2001
DOI: 10.1021/ac010133i
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Chemiluminescent Behavior of Pharmaceuticals and Pesticides

Abstract: The present paper deals with the first attempt to apply molecular connectivity calculations to predict a chemical property with analytical usefulness: the chemiluminescent behavior of substances when reacted with common oxidants in a liquid phase. Preliminary evidence when searching for new direct CL methods consisted of the examination of analyte reaction with a wide range of oxidants and media. This task, which results in time-consuming and trial-and-error expensive procedures, is necessary due to ensure emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A gas chromatography-mass spectrometry method was also described for the determination of a number of drugs including the proposed compounds (16). Also the chemiluminescent behaviors of both diuretics and other diuretics were studied (17).…”
Section: Introductionmentioning
confidence: 99%
“…A gas chromatography-mass spectrometry method was also described for the determination of a number of drugs including the proposed compounds (16). Also the chemiluminescent behaviors of both diuretics and other diuretics were studied (17).…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography-mass spectrometry (GC-MS) method was described for determination of a number of drugs including HCT, SPR and chlorothiazide (HCT process impurity). [16] Lahuerta-Zamora et al [17] studied the chemiluminescent behaviours of several diuretics, including HCT and SPR.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, many publications have reported the application of quantitative structure–property relationships (QSPR) in describing the physical properties and biological activity of chemicals, and all results have shown that the QSPR models can clearly indicate the molecular structure of the related chemicals. The common method used in QSPR is the molecular connectivity index (MCI), , and many research papers can be found relating properties of organic compounds using the QSPR model in recent years.…”
Section: Introductionmentioning
confidence: 99%